Correction to: Tailored message interventions versus typical messages for increasing participation in colorectal cancer screening among a non-adherent population: A randomized controlled trial - Kei Hirai; Yoshiki Ishikawa; Jun Fukuyoshi; Akio Yonekura; Kazuhiro Harada; Daisuke Shibuya; Seiichiro Yamamoto; Yuri Mizota; Chisato Hamashima; Hiroshi Saito (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.